The impact of knowledge creation on employee engagement from the perspectives of exploitation and exploration - Irene, Wei Kiong Ting; Sui, Hai Juan; Qian, Long Kweh; Liu, Yao (2018)
Employee engagement is increasingly important in today’s competitive society because organizational competitiveness requires knowledge. Tacit knowledge, which resides in employees, is particularly essential, and it cannot be obtained unless employees are engaged in managing knowledge. However, studies on employee engagement from the perspective of knowledge creation are rare. The main purpose of this study is to assess the impacts of knowledge creation on employee engagement. After identifying that knowledge creation could facilitate employee engagement from a literature review, the study proposed a model of knowledge creation toward employee engagement. A survey questionnaire was developed accordingly. With a stratified sampling method, data were collected from the academic staff of one public and one private university located in Malaysia. A total of 200 academic staff members participated in this study. Linear regression analysis was performed to test how knowledge creation (i.e., exploration and exploitation) affects employee engagement. Statistical results show that the exploration and exploitation of knowledge creation positively and significantly affect employee engagement. The proposed framework could aid universities in utilizing knowledge creation practices to engage employees so as to attain and sustain competitive advantage.